Cotoneaster (Cotoneaster Medik.) – new object of biotechnology - Михайлова, І. С.; Гревцова, Г. Т.; Гаркава, К. Г. (Problems of Environmental Biotechnology, 2016)
The influence of the water-salt extracts of Cotoneaster buds and foliages Series Adpressi, Melanocarpi, Salicifoli on functional activity of the phagocyte were studied by us. It is recommended to use their foliages as a source of effective adaptive substances.